Biophysical, psychrometric and physiological limits for continuous liquid and air-based personal cooling systems in working men: A case for amending ASTM2300-10(2016). (December 2020) - Bach, Aaron J.E.; Borg, David N.; Minett, Geoffrey M.; Maley, Matthew J.; Stewart, Ian B.
Highlights: The reported efficacy of cooling systems may not be replicated outside their tested environment. As the composition of the environment can influence a cooling systems heat loss potential. ASTM F2300-10(2016) should present a variety of environments rather than a one size fits all approach. Abstract: The ASTM F2300-10 standard testing protocol was implemented for two continuous personal cooling systems (venturi air vest and cold-water perfused vest) with theoretically similar cooling capacities. Secondly, we used the same systems in step-wise increments of either temperature or relative humidity in order to define the upper limit of the prescriptive zone for each (i.e., critical environmental limits method). ASTM F2300-10 standard protocol saw both vests equally effective in reducing cardiovascular and thermal strain relative to a no cooling control. The critical environmental limits method saw the upper limit for humidity significantly increase in both vests, with no differences between the vests. However, the upper limit for temperature was increased in the cold-water vest, with the venturi air vest being no more beneficial than the control. Overall, this study used an evidence-based approach to demonstrate that a single environment, as per ASTM F2300-10, failed to delineate differences between continuous cooling systems promoting discrete mechanisms of heat loss. Most notably, relative to no cooling, the use of the air vest provided no additional evaporative cooling in a low humidity environment, and therefore no increase in the upper limits of critical temperature. This should highlight to end users not to assume that one size fits all for effective personal cooling systems if applied outside of the environment it was tested. Based on these findings, we suggest a range of environments be recommended by the ASTM F2300-10 standard for the evaluation of cooling systems to ensure systems ineffective in certain environments can be identified.